Using Target Costing in Implementation Confrontational Strategy Applied study in General Company for Electronic Industries - فرج, مشتاق كامل (Journal of Economics and Administrative Sciences, 2012)
This research has come out with that strategies made by Porter as generally strategies applicable to any size and type of economic units cannot be applied to many of the economic units in the world in generally and in Iraq especially not a lot of economic units have the resources and competencies that enable them to provide a unique product of its kind in the minds of customers and then adopt a differentiation strategy  and not a lot of economic units have the resources and competencies that make them the cost leader. Differentiators and cost leaders are minority in the world while not differentiators and not cost leaders are majority in the world.The economic units are not differentiators and not cost leaders should adopt a strategy of confrontation and compete with each other through the characteristics of the three main product, or the so-called survival triplet a cost, quality and functionality grappling competitors through the trilogy is one of the possible economic unity to survive and continue to successfully in the industry. The research also concluded that the target costing is cost effective tool that will enable economic units have access to cost, quality and functionality offered by the competitors and then to achieve competition in the trilogy to survive and finally applying confrontation strategy.